Real-world experience of women using extended-cycle vs monthly-cycle combined oral contraception in the United States: the National Health and Wellness Survey - Rossella E. Nappi; Iñaki Lete; Lulu K. Lee; Natalia M. Flores; Marie-Christine Micheletti; Boxiong Tang (BMC, 2018)
Abstract Background The real-world experience of women receiving extended-cycle combined oral contraception (COC) versus monthly-cycle COC has not been reported. Methods Data were from the United States 2013 National Health and Wellness Survey. Eligible women (18-50 years old, premenopausal, without hysterectomy) currently using extended-cycle COC (3 months between periods) were compared with women using monthly-cycle COC. Treatment satisfaction (1 "extremely dissatisfied" to 7 "extremely satisfied"), adherence (8-item Morisky Medication Adherence Scale©), menstrual cycle-related symptoms, health-related quality of life (HRQOL) and health state utilities (Medical Outcomes Short Form Survey-36v2®), depression (9-item Patient Health Questionnaire), sleep difficulties, Work Productivity and Activity Impairment-General Health, and healthcare resource use were assessed using one-way analyses of variance, chi-square tests, and generalized linear models (adjusted for covariates). Results Participants included 260 (6.7%) women using extended-cycle and 3616 (93.3%) using monthly-cycle COC. Women using extended-cycle COC reported significantly higher treatment satisfaction (P = 0.001) and adherence (P = 0.04) and reduced heavy menstrual bleeding (P = 0.029). A non-significant tendency toward reduced menstrual pain (39.5% versus 47.3%) and menstrual cycle-related symptoms (40.0% versus 48.7%) was found in women using extended-cycle versus monthly-cycle COC. Significantly more women using extended-cycle COC reported health-related diagnoses, indicating preferential prescription for extended-cycle COC among women reporting more health problems. Consistent with this poorer health, more women using extended-cycle COC reported fatigue, headache, and activity impairment (P values < 0.05). There were no other significant differences between groups. Conclusions This real-world observational study supports extended-cycle COC as a valuable treatment option with high satisfaction, high adherence, and reduced heavy menstrual bleeding.